Certain Results for the 2-Variable Peters Mixed Type and Related Polynomials (Analysis in Theory and Applications, 2018)
In this article, the 2-variable general polynomials are taken as base with Peterspolynomials to introduce a family of 2-variable Peters mixed type polynomials.These polynomials are framed within the context of monomiality principle and theirproperties are established. Certain summation formulae for these polynomials are alsoderived. Examples of some members belonging to this family are considered and numbersrelated to some mixed special polynomials are also explored.
Keywords: 2-Variable general polynomials; Peters polynomials; 2-variable truncated exponential polynomials; Sheffer sequences; monomiality principle.